DETERMINAN KEPUASAN KERJA PEGAWAI: MOTIVASI, KOMUNIKASI DAN STRES KERJA - Ika Fitriyani; Nonny Desti Muryani (Samalewa: Jurnal Riset & Kajian Manajemen, 2023)
This study aims to determine the factors that influence employee job satisfaction at the Agriculture Office of Sumbawa Regency which consists of work motivation, communication, and work stress. This type of research is associative research. The type of data used is quantitative data obtained directly by researchers from primary sources through questionnaires The population in this study amounted to 50 people, so all members of the population were used as samples so that this research was categorized as a population study or using a census sampling technique. All data were processed using the SPSS program to be studied using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determination coefficient test (R2). The results of this study indicate that work motivation, communication, and work stress have a positive and significant effect on employee job satisfaction at the Agriculture Office of Sumbawa Regency, either partially or simultaneously. The degree of influence of the variables of work motivation, communication, and work stress on the variable of employee job satisfaction at the Sumbawa Regency Agriculture Office is 55.6%, while the remaining 44.4% is influenced by other variables outside this research model, such as competence, leadership style, work culture, work environment, and others.